Serum uric acid levels predict the development of albuminuria over 6 years in patients with type 1 diabetes: Findings from the Coronary Artery Calcification in Type 1 Diabetes study - Jalal, Diana I. (Oxford University Press, 2010)
Background. Recent studies suggest that uric acid is a mediator of diabetic nephropathy. We hypothesized that elevated serum uric acid levels are a strong predictor of albuminuria in patients with type 1 diabetes. Methods. We analyzed data from the Coronary Artery Calcification in Type 1 Diabetes study, a prospective observational study. A stepwise logistic regression model was applied to predict the development of micro- or macroalbuminuria after 6 years of follow-up in 324 participants who had no evidence of micro- or macroalbuminuria at baseline. A P-value <0.1 was used as the criteria for entry into and removal from the model. Results. The following factors were selected in the stepwise multivariate model as predictors of micro- or macroalbuminuria at the 6-year follow-up visit: baseline serum uric acid levels, HbA(1c) and pre-albuminuria. For every 1-mg/dl increase in serum uric acid levels at baseline, there was an 80% increased risk of developing micro- or macroalbuminuria at 6 years (odds ratio 1.8; 95% confidence interval 1.2, 2.8; P = 0.005). Additional covariates considered in the stepwise model were sex, age, duration of diabetes, angiotensin-converting enzyme inhibitor or angiotensin II receptor blocker treatment, waist circumference, waist/hip ratio, body mass index, systolic and diastolic blood pressure, smoking, serum creatinine, cystatin C, high-density lipoprotein cholesterol and triglycerides. Conclusion. Elevated serum uric acid levels are a strong predictor of the development of albuminuria in patients with type 1 diabetes.